The effectiveness of cognitive rehabilitation on executive function and working memory function in the elderly with non-clinical depression - Shafaei, Shahrzad; Mirzaian, Bahram; Hasanzadeh, Ramezan (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of this study was to determine the effectiveness of cognitive rehabilitation on executive function and working memory function in the elderly with non-clinical depression. Methods: The current research was an applied research and in terms of the research method, it was a semi-experimental type of pre-test-post-test and follow-up research with a control group. The statistical population of this research includes all elderly people suffering from non-clinical depression, 90 men and women who visited the Mehrgan counseling center between January 2020 and June 2021. The study sample was 30 elderly people who were selected by purposeful sampling and randomly divided into two equal intervention and control groups (15 people in each group). The follow-up period was conducted three months after the completion of the post-test. Cognitive rehabilitation treatment sessions were conducted in ten one-hour sessions weekly based on the protocol of Schulberg and Matir (2001). The data in this research was obtained by using the Beck II depression questionnaire (Beck, Steer and Brown, 1996), the executive function questionnaire, the working memory function questionnaire: by Valat Ezuvi, Pradat Dale and Ezuvi (2012). In this research, repeated measurement test and SPSS.22 software were used. Results: The results showed that cognitive rehabilitation on executive function (F=49.86, P